Balanced Nutritious Diet and Limited Gadget Use to Optimize Stunting Prevention: Balanced Diet and Limited Gadget Use in Stunting Prevention - Juwita (CV. Paperhome Indonesia, 2025)
Background: In Indonesia, based on the 2019 Basic Health Research (Riskesdas), the nutritional status of toddlers with stunting was 37.2%. The prevalence of stunting did not show any decrease or improvement compared to 2020 (35%) and 2021 (36.8%). Based on data from the 2023 Indonesian Health Survey (SKI), the prevalence of stunting in Makassar increased from 18.04% to 25.6%, a 7.2% increase. This situation presents a major challenge for all parties, including the government, health services, health workers, the community, and the private sector, to collaborate in achieving the target of reducing stunting rates to 14% by 2024. Objective: To determine the effect of a balanced, nutritious diet without gadgets on stunting prevention at the Tamangapa Community Health Center. Method: Objective: To determine the effect of a balanced, nutritious diet without gadgets on stunting prevention at the Tamangapa Community Health Center. The population in this study was 30 respondents. The sampling technique used was total sampling, with 30 respondents included in the study. Results: Of the total 30 toddlers (100%), 20 toddlers (66.7%) had good dietary pattern suitability but were given gadgets, 0 toddlers (0%) had good weight gain without being given gadgets, 5 toddlers (16.7%) had moderate dietary suitability without gadgets, 3 toddlers (10%) had poor dietary suitability, and 2 toddlers (6.6%) had poor dietary suitability without gadgets. Data analysis using Fisher's Exact Test showed a p-value of 0.020, indicating a significant relationship between a balanced nutritional diet and the provision of gadgets in relation to stunting prevention (p < 0.05). Conclusion: There is a significant relationship between a balanced nutritious diet without gadgets and stunting prevention among 30 toddlers at the Tamangapa Community Health Center (Posyandu RW 1). A good and appropriate diet can support optimal growth and development in toddlers aged 1–5 years. A balanced diet without gadgets significantly influences toddlers’ weight and height growth.